(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
Economics of poverty is an international programme organized during the years 2017-2020 in Rome, Madrid and Milano, supported and financed by the Ecole française de Rome and the Casa de Velazquez and some universities. It aimed to study poverty considered as an economic phenomenon, and to enlighten its causes and its effects on singular individuals and social groups. Two publications will follow its ending in 2021-2022.